Be bad but (still) look good: Can controversial industries enhance corporate reputation through CSR initiatives?. (8th March 2018) - Aqueveque, Claudio; Rodrigo, Pablo; Duran, Ignacio J.
Abstract : Even though the link between perceived corporate social responsibility fit (PCSR‐fit) and corporate reputation has received much attention from scholars, this tradition has ignored that the underpinnings of this association vary depending on the particular characteristics of each industry under study. To delve into this matter, we investigate in the increasingly relevant context of controversial industries (CIs) how PCSR‐fit could enhance corporate reputation and which are the mediating mechanisms of this association. Our academic contribution is twofold. First, we find that controversial sectors indeed can increase corporate reputation through CSR activities. However, we find that to achieve this goal, the nature of PCSR‐fit should be different than what extant literature indicates, because companies in these settings should directly focus on avoiding or reducing their inherent controversial harm or impact. Second, we evidence that "CSR initiatives' legitimacy" and "situational skepticism" mediate the PCSR‐fit and corporate reputation relationship in CIs. Therefore, we further unravel the underpinnings of this association to advance what we know on the matter and aid practitioners in this particular context.